A near infrared fluorescent probe for naked eye visualization and selective detection of hydrogen sulfide. (2022) - Sureshkumar, Kempahanumakkagari; Ramakrishnappa, T.
Abstract: A napthofluoresciene based NIR fluorescent probe for sulfide was synthesized and characterized by nmr and ESI-MS spectrometry. The present probe can act as rapid, colorimetric and NIR fluorescent turn on sulfide sensor at nano molar levels. It is highly selective to sulfide over other reducing agents like sulfate, sulfite and also thiol moieties. It has been successfully applied for the determination of sulfide in various environmental water samples.